Wykorzystanie e-learningu jako formy kształcenia zdalnego na publicznych uczelniach wyższych w Polsce - Hołowiecki, Marek (Wydawnictwo Instytutu Filozofii UAM, 2014)
The article discusses various e-learning systems in Polish public higher education. A questionnaire has been prepared to obtain answers from all Polish public universities and several other higher education institutions. The research revealed some interesting tendencies (e.g. the majority of institutions have applied free and open source solutions) and established some important data dependencies (e.g. the majority of teachers have been trained in applying these systems). The paper investigates the extent to which Open Access features are implemented in major e-learning platforms in Poland. There is hardly any Polish literature on these issues. This study concludes with certain suggestions concerning various possible developments in new and existing e-learning platforms in Polish universities.
Keywords: E-learning; Computer Technology; Higher Education in Poland; Open Access; Information Technology